DEVELOPMENT OF FLIPBOOK-BASED INSTRUCTIONAL MATERIALS INTEGRATED WITH VIRTUAL REALITY FOR LOWER PLANT BOTANY LEARNING - Advend Sri Rizki Sianturi; Sendy Putra Pradana (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study aimed to develop flipbook-based instructional materials assisted by Virtual Reality (VR) for the Lower Plant Botany. The research employed a Research and Development (R&D) approach using the 4D model, consisting of define, design, develop, and disseminate stages. At the define stage, a preliminary field exploration and identify lower plant species as learning content. Data were obtained through direct observation and morphological identification of lower plant. The design stage involved developing instructional materials using flipbook and Virtual Reality media based on field data. The development stage included expert validation, product revision, and limited trials with Biology Education students to evaluate feasibility and practicality. The disseminate stage was carried out through limited implementation in lectures and distribution of the developed materials. The results indicated that the developed instructional materials were feasible based on expert validation. Expert validation indicated that the instructional materials were feasible across content, presentation, language, and scientific aspects (75–88.3%), while media validation demonstrated a very high feasibility level (99.07%). These findings indicate that flipbook-based instructional materials integrated with Virtual Reality offer an engaging and immersive learning solution that enhances students’ understanding of abstract and microscopic concepts in Lower Plant Botany while supporting scientific and digital literacy.